ADHD - Strong, Jeff; MacHendrie, Carol (--For dummies., 2024)
"Attention deficit hyperactivity disorder (ADHD) is one of the most globally prevalent neurodevelopmental disorders. ADHD For Dummies explores living a healthy and fulfilling life with ADHD, from seeking diagnosis to choosing the right treatment path for you or your loved one. You'll read about the latest in ADHD research, equipping you with valuable knowledge as you care for a child with ADHD or explore your own ADHD symptoms as an adult. This book provides the answers you need on how to deal with day-to-day challenges at home, school, and work, and how to find support and counseling. With appropriate management, anyone can live a great life with ADHD. Learn what ADHD is--and what it isn't. Get up to date with the latest information on ADHD, including medications and non-medical treatments. Find the right professional to help you get the support you or your children need. This is the perfect Dummies guide for both parents of children with ADHD and adults with ADHD looking to learn more. Teachers, counselors, and therapists--this is also a great resource to educate yourself and your clients"--